2016
DOI: 10.1016/j.jacc.2016.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Thrombosis and Major Bleeding After PCI With Drug-Eluting Stents

Abstract: Simple risk scores of baseline clinical variables may be useful to predict risks for ischemic and bleeding events after PCI with DES, thereby facilitating clinical decisions surrounding the optimal duration of DAPT. (Patterns of Non-Adherence to Anti-Platelet Regimen in Stented Patients [PARIS]; NCT00998127).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
344
4
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 484 publications
(376 citation statements)
references
References 31 publications
16
344
4
4
Order By: Relevance
“…11,26 This variable was also not considered as candidate predictor for risk model building in PARIS registry (Patterns of Non-Adherence to Dual Anti-Platelet Regimen in Stented Patients). 27 Results from the present study suggested that the early discontinuation of P2Y 12 inhibitors even after newer-generation DES implantation may be associated with a risk of developing subsequent myocardial infarction (mainly nonstent thrombosis related) in patients with multivessel disease. This phenomenon was prominent in patients who presented with acute coronary syndrome but not in those who presented with stable coronary artery disease.…”
Section: Discussionmentioning
confidence: 59%
“…11,26 This variable was also not considered as candidate predictor for risk model building in PARIS registry (Patterns of Non-Adherence to Dual Anti-Platelet Regimen in Stented Patients). 27 Results from the present study suggested that the early discontinuation of P2Y 12 inhibitors even after newer-generation DES implantation may be associated with a risk of developing subsequent myocardial infarction (mainly nonstent thrombosis related) in patients with multivessel disease. This phenomenon was prominent in patients who presented with acute coronary syndrome but not in those who presented with stable coronary artery disease.…”
Section: Discussionmentioning
confidence: 59%
“…previous revascularization) or at high risk of major bleeding (based on age, body mass index, smoking, anemia, renal function, and whether on an anticoagulant in addition to antiplatelet therapy). 128 In patients considered for long-term dual antiplatelet administration, the DAPT score (dual antiplatelet therapy; based on age, smoking, diabetes, MI at presentation, prior MI or percutaneous coronary intervention, stent type and diameter and heart failure) may provide a way of categorizing patients who are likely to receive a favorable net benefit from long-term DAPT, related to high ischemic risk and lower bleeding risk.…”
Section: Optical Coherence Tomography Plaque Rupturementioning
confidence: 99%
“…[32,33] Major cardiovascular events and mortality rates in the BVS-treated patients in our cohort were similar or even lower than in patients treated with other stents. Moreover, patients treated with BVS in our study had a higher number of vessels with significant lesions, and subsequently received more stents.…”
Section: [11]mentioning
confidence: 54%